O (des)tecer de narrativas: A metaficção no romance e filme the french lieutenant's woman - Oliveira, Carlos André Cordeiro de (2015)
This dissertation proposes a comparative analysis of metafiction in the novel The French lieutenant's woman, by John Fowles and in the film with the same name, directed by Karel Reisz, with screenplay by Harold Pinter. Our theoretical frame highlights some of the main studies published in the field of metafiction. We supplement the investigation of metafiction in the literary and filmic narrative in interface with other theoretical contributions, among them: narratology, filmic adaptation and some theoreticians of postmodernism. We adopt as a methodological principle the comparative investigation of some aesthetic devices and procedures associated with metafiction (self-reflexivity, self-consciousness, intertextuality, mise-en-abyme, among others) as long as they have been emphasized in the appreciation of some selected narrative categories (narrator, epigraph, character, reader/spectator) in the literary and filmic contexts. As a whole, our results consider metafiction as being a privileged, mediatory, logic, processual and theoretical-critical tool for the in-depth comprehension of the filmic and literary narratives.